Higher Salt Hydrophobicity Lengthens Ionic Wormlike Micelles and Stabilizes Them upon Heating - Isabettini, Stephane (Langmuir : the ACS journal of surfaces and colloids, 2021)
Tuning the rheological properties of surfactant solutions by charge screening is a convenient formulation tool in cosmetic, household, oil recovery, drag-reduction, and thickening applications. Surfactants self-assemble in water, and upon charge screening and core shielding, they grow into long wormlike micelles (WLMs). These are valuable model systems for soft matter physics, and the most explored formulation is hexadecyl-trimethylammonium bromide (CTAB) and sodium salicylate (NaSal). Replacing NaSal with aromatic salts of altered hydrophobicity results in different penetration of the additive in the CTAB micellar core. This altered penetration depth will determine the anisotropic micellar growth that tailors the viscoelastic response. Sodium 4-methylsalicylate (mNaSal) is a higher hydrophobicity alternative to NaSal, requiring less additive to induce strong changes in the viscoelastic properties. Herein, we provide a comparative study of the mNaSal/CTAB system with the reference NaSal/CTAB over a range of temperatures and salt concentrations. The findings from the well-known NaSal/CTAB pair are transferred to the mNaSal/CTAB system, revealing the origins of the WLM solution's viscoelastic properties by discerning contributions from charge screening and micellar core shielding upon small differences in hydrophobicity